2021
DOI: 10.1371/journal.pone.0256745
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent behavioural plasticity compromises disruptive selection of sperm traits in squid

Abstract: Sperm morphology is generally uniform within a species due to selective pressures that act to achieve better fertilization outcomes under postcopulatory competitive circumstances. Therefore, polyandry that intensifies post-mating sperm competition should constrain intraspecific sperm polymorphism. Contrary to this paradigm, we previously found that a polyandrous squid, Heterololigo bleekeri, produces dimorphic eusperm (flagellum length dimorphism; FLD), which is closely associated with alternative reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, some loliginid squid species also show context-dependent ARTs 22 , 37 40 , where males flexibly change mating tactics in response to relative size differences between mating pairs 22 , 39 , which resulted in attenuated sperm dimorphism 40 . In any case, males must choose the designated areas of female body locations, because the insemination site greatly influences the fertilization success (but see 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some loliginid squid species also show context-dependent ARTs 22 , 37 40 , where males flexibly change mating tactics in response to relative size differences between mating pairs 22 , 39 , which resulted in attenuated sperm dimorphism 40 . In any case, males must choose the designated areas of female body locations, because the insemination site greatly influences the fertilization success (but see 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in squid, the morphological traits of sperm are generally considered to be adaptive to the insemination environments and their associated sperm storage modes 36 . However, some loliginid squid species also show context-dependent ARTs 22,[37][38][39][40] , where males flexibly change mating tactics in response to relative size differences between mating pairs 22,39 , which resulted in attenuated sperm dimorphism 40 . In any case, males must choose the designated areas of female body locations, because the insemination site greatly influences the fertilization success (but see [41][42][43][44] ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if they initially mature as a sneaker and switch to a consort tactic as they grow up, immature males larger than sneakers would not be observed during the reproductive season. Hirohashi et al [ 27 ] presumed the ARTs of H. bleekeri to be fixed because their reproductive traits are clearly dimorphic and no intermediate males were identified, unlike in D. plei [ 21 , 23 ]. Our result, indicating that most immature males had probably already determined their life-history pathway as a result of their hatch date, provides more direct support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also observed the growth history of H. bleekeri , but the environmental factors involved still remain to be determined, as do the ways in which they exert their influence based on hatch date to affect ART determination in H. bleekeri . In this species, distinct dimorphisms in reproductive traits, such as the form of spermatangia and sperm morphology, have been observed [ 25 27 , 51 ], and differences in gene expression have also been identified between the spermatozoa of consorts and sneakers [ 52 ]. Further epigenetic and endocrine studies to understand how the difference in hatch date influences the regulatory cascades underlying the phenotypic variation will help to further elucidate the mechanism of ART determination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation